ADDIE-Based Development of a Solar-Powered Sprayer for Efficient Weed Control in Remote Oil Palm Plantations - Abdul Manab; M Bahrul Muttaqin; Andre Rabiula; Ramadhani, Salisa 'Asyarina; Yosi Riduas Hais; Dasrinal Tessal (Jurusan Teknik Elektro Universitas Andalas, 2025)
Oil palm plantations in Indonesia demand efficient weed control methods, particularly for large-scale operations in remote areas. Manual pesticide sprayers are still commonly used, but they require high labor, long operating time, and are not energy-efficient. This study presents the design and development of a solar-powered pesticide sprayer using the ADDIE method—Analysis, Design, Development, Implementation, and Evaluation. The prototype consists of a 50 Wp monocrystalline solar panel, two 12V 24Ah VRLA batteries, a DC pump with variable pressure levels, and an Automatic Transfer Switch (ATS) for alternating battery use. The system is mounted on a frame suitable for motorcycle transport to improve field mobility and adaptability in plantation environments. Development followed all ADDIE phases and was validated through real-world field testing. Results showed a 75% reduction in spraying time—from 8 hours (manual) to 2 hours—with a maximum pressure of 70 PSI and a spray reach of 3.5 meters. The ATS allowed uninterrupted operation under varying sunlight conditions. This design offers greater energy efficiency, continuous usability, and flexible deployment compared to similar systems. The findings demonstrate the feasibility of applying solar energy to support sustainable weed management in off-grid agricultural settings, highlighting its potential for broader agricultural mechanization.